Synthesis of N'-Substituted-2-((5-(4-Chlorophenyl)-1,3,4-Oxadiazol-2-ylthio Acetohydrazie Derivatives as Suitable Antibacterial Agents - Akhtar, Muhammad Nadeem; Rasool, Shahid; Rehman, Aziz-ur; Abbasi, Muhammad Athar (Pharmacotherapy Group, 2015)
Purpose: To evaluate antibacterial activity of a series of molecules bearing 1,3,4-oxadiazole and azomethine moieties. Methods: The 4-chlorobenzoic acid (1) was precursor to N'-substituted-2-(5-(4-chlorophenyl)-1,3,4- oxadiazol-2-ylthio)acetohydrazide, 8a-p, through a multistep synthesis of corresponding ester, 2, hydrazide, 3 and 1,3,4-oxadiazole, 4. The molecule, 4, was subjected to electrophilic substitution by ethyl-2-bromoacetate to yield 5 which was stepped to 2-(5-(4-chlorophenyl)-1,3,4-oxadiazol-2- ylthio)acetohydrazide (6). The target molecules, 8a-p, were synthesized by nucleophilic addition of 6 to arylaldehydes, 7a-p. The proposed structures of all the synthesized molecules were elucidated by Infra Red (IR), Proton Nuclear Magnetic Resonance (1H-NMR) and Electron Impact Mass Spectrometry (EIMS) spectral data. Antibacterial activity was evaluated by the principle that microbial growth is in a log phase of growth and so results in increased absorbance of broth medium which is observed. Results: The molecule, 8b, was active against S. aureus and 8c against S. typhi only. The molecule, 8p, was the most active against S. typhi with minimum inhibitory concentration (MIC) value of 10.04 ± 1.25 μM while 8e was active against E. coli with MIC of 9.45 ± 1.00 μM, both relative to the reference standard, ciprofloxacin, which displayed MIC of 9.13 ± 2.00 and 8.90 ± 1.65 μM, respectively. Conclusion: Most of the synthesized molecules exhibit 50 % antibacterial activity relative to the reference. Molecules 8b and 8c are the least active compounds.